2017
DOI: 10.1016/j.jval.2017.08.276
|View full text |Cite
|
Sign up to set email alerts
|

Association of Health-Related Quality of Life (HRQOL) and Healthcare Resource Utilization (HCRU) in Checkmate 141, A Phase 3 Study of Nivolumab Versus Investigator’s Choice (IC) in Patients with Recurrent or Metastatic (R/M) Platinum-Refractory Squamous Cell Carcinoma of The Head and Neck (SCCHN)

Abstract: Objectives: Reviewing the statistical indicators of mortality we see that cancer is in second most common cause of death after cardiovascular diseases. Cervical cancer is the seventh most common type of cancer (among women) in Europe. According to current estimations, there are 58,373 new diagnosed out of 3,257 million women older than 15 years, from which 24,404 ends with death. There is an organized screening system in Hungary since 2003. Most women participate "traditionally", out of this system or ignore i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…An exploratory analysis found that some HRQoL measures correlated with healthcare resource utilization (HCRU; frequency of physician office visits, hospital outpatient visits, emergency department visits, hospital admissions, or other visits) [42]. Higher baseline EORTC QLQ-C30 global health status (p = 0.040), cognitive functioning (p = 0.012), and social functioning (p = 0.011) were associated with lower total HCRU event frequency, while higher symptom burden was associated with more frequent total HCRU events.…”
Section: Squamous Cell Carcinoma Of the Head And Neckmentioning
confidence: 99%
See 1 more Smart Citation
“…An exploratory analysis found that some HRQoL measures correlated with healthcare resource utilization (HCRU; frequency of physician office visits, hospital outpatient visits, emergency department visits, hospital admissions, or other visits) [42]. Higher baseline EORTC QLQ-C30 global health status (p = 0.040), cognitive functioning (p = 0.012), and social functioning (p = 0.011) were associated with lower total HCRU event frequency, while higher symptom burden was associated with more frequent total HCRU events.…”
Section: Squamous Cell Carcinoma Of the Head And Neckmentioning
confidence: 99%
“…For some indications, PROs may distinguish between available therapies when comparative clinical data are not available, enabling physicians and patients to make informed therapeutic decisions. PROs have prognostic capacity, which could be useful for tailoring therapeutic approaches to patient needs [39,40,42].…”
Section: Relevance and Limitations Of Pro Assessmentsmentioning
confidence: 99%